Sir Matthew Tierney and the foundation of the 1804 Sussex Vaccine Institution. (May 2020) - Cooper, Maxwell J; Morris, Hilary; Whiston, Benjamin
Irish physician Sir Matthew John Tierney (1776–1845) was a vaccine pioneer who learnt the procedure directly from Edward Jenner in Gloucestershire. In 1802 Tierney completed an MD at Glasgow on vaccination and moved to Brighton, where he was appointed physician to the Prince of Wales (the future King George IV). This paper considers Tierney's role in the foundation of the 1804 Sussex Vaccine Institution. Tierney was the first president of the Institution's Medical Council. His leadership lay in his knowledge of vaccination (including transporting cowpox material) and his close relationship with the Prince of Wales. The Institution's official name was the Royal Sussex Jennerian Society for the Extermination of the Small-pox and offered vaccination at 16 stations across the county and one in Kent. Vaccination was undertaken by local surgeons at their houses at set hours. In its first year, the Institution vaccinated 946 individuals, of whom 509 for free. Despite this, concerns were raised over uptake by poorer members of society. The Institution's Brighton station was probably absorbed into the new 1809 dispensary. Tierney's promotion of vaccination and instructions for new practitioners represent the embryonic beginnings of evidence-based medicine and modern medical education in Brighton.